War by others' means delivering effective partner force capacity building - Watling, Jack; Reynolds, Nick (Whitehall papers, 2020)
A new era of great power competition places a strategic premium on the efficiency with which states can pursue their aims. There is therefore likely to be an expanded scope for partnered operations. Partner force capacity building has a long history, with very mixed results, yet there is little historical memory in the institutions tasked with carrying it out. War by Others' Means uses archival research, interviews with practitioners, and observation of capacity building to understand why states undertake it, how they should select, train and equip their partners, and how they should manage the generation and withdrawal of trainers.